2007
DOI: 10.1002/adfm.200700278
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Geoinspired and Synthetic Chrysotile Nanotubes by Atomic Force Microscopy and Transmission Electron Microscopy

Abstract: Geoinspired synthetic chrysotile nanotubes both stoichiometric and 0.67 wt % Fe doped were characterized by transmission electron microscopy and electron diffraction. Bending tests of the synthetic chrysotile nanotubes were performed using the atomic force microscope. The nanotubes were found to exhibit elastic behaviour at small deformations (below ca. 20 nm). Young's modulus values of (159 ± 125) GPa and (279 ± 260) GPa were obtained from the force‐deflection curves using the bending equation for a clamped b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 32 publications
3
56
0
Order By: Relevance
“…In fact, octahedral coordinated Fe has been observed in all the substitution range in Fe-doped chrysotile synthesized in absence of metallic Fe. On the contrary, tetrahedral coordinated Fe inducing a flattening of the chrysotile structure appears prevalent in respect of octahedral coordinated Fe in highly Fe-doped chrysotile synthesized when metallic Fe is available in the synthetic environment [19,[21][22][23]. The position of the sites responsible for catalytic and redox activity of Fe of asbestos is currently unknown, even if the fibre surface appears mainly to control the Fe reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, octahedral coordinated Fe has been observed in all the substitution range in Fe-doped chrysotile synthesized in absence of metallic Fe. On the contrary, tetrahedral coordinated Fe inducing a flattening of the chrysotile structure appears prevalent in respect of octahedral coordinated Fe in highly Fe-doped chrysotile synthesized when metallic Fe is available in the synthetic environment [19,[21][22][23]. The position of the sites responsible for catalytic and redox activity of Fe of asbestos is currently unknown, even if the fibre surface appears mainly to control the Fe reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…The first note concerning the tubular structure of chrysotile was by Pauling (1930) who suggested that the Mg-analogue of kaolinite should have a curved structure because of the misfit between the octahedral and tetrahedral sheets [36]. Later investigators confirmed this hypothesis and the tubular structure of chrysotile was demonstrated by electron diffraction and transmission electron microscopy (TEM) [37].…”
Section: Nanotubes With a Chrysotile Structurementioning
confidence: 99%
“…Chrysotile (Piperno et al, 2007;Anbalagan et al, 2010) can be synthesized in aqueous solution under mild conditions, easily modified (Wypych et al, 2004;Wang et al, 2006;Wang et al, 2009) and functionalized (Nakagaki & Wypych, 2007). Therefore chrysotile is an interesting target material to be used as component of hybrid materials, support for catalysis, ionic channels, molecular sieving, for gas storage Nakagaki & Wypych, 2007) and other applications in nanotechnology.…”
Section: Chrysotile Nanotubes -Structural Propertiesmentioning
confidence: 99%
“…The results have shown that chrysotile NTs exhibit elastic behavior at small deformation. The chrysotile Young's modulus evaluated by (Piperno et al, 2007) et al (2009) have studied the stability and structural properties of some armchair chrysotile NTs using the DFT method and helical symmetry approach as it is implemented in the CRYSTAL program . The structural results are in good agreement with the experimental data for NTs and lizardite monolayer.…”
Section: Chrysotile Nanotubes -Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation